Fluid Management Knowledge and Inter-Dialytic Weight Gain (IDWG) in Chronic Kidney Disease Who Undergo Haemodialysis Treatment: Literature Review - Yurisca Maqfiroh; Bayhakki Bayhakki; Oswati Hasanah (Universitas Muhammadiyah Tangerang, 2021)
Chronic kidney disease (CKD) is a condition where the kidney has decreased in the main function in the blood filtration process marked by the value of Glomerular Filtration Rate (GFR) lower than 60 ml/minute/ 1,73 m2 for approximately 3 months. This study aims to conduct a systematic review of research articles that evaluate the knowledge of fluid management and Inter-Dialytic Weigh Gain (IDWG) in hemodialysis patients. The design of this research is the literature review. The research article was conducted through scientific databases such as Research Gate, Pubmed, Google Scholar, and Science Direct. The paper should be released in 2016-2020 include national and international publishing. In the paper searching process, writer used 2 kinds of keywords in a different language which is Bahasa Indonesia and English, the keywords are knowledge, fluid management, IDWG, and HD patients. There are 2.764 papers matched with the keywords and conducted the selections process using inclusion, exclusion criteria, and JBI Critical Appraisal. We found 7 papers include 5 different countries which are Indonesia, Turkey, UK, Japan, and US. Based on 7 articles, it was found 5 studies were obtained fluid management knowledge, it showed the majority of respondents having moderate and high knowledge. Four articles were obtained about IDWG and the majority having moderate and mild IDWG. Respondent characteristics were influenced by fluid management knowledge and IDWG adherence. For further research, it is recommended to discuss more about factors affected fluid management knowledge and the relationship between motivation, knowledge, and IDWG.